Analysis of Somaclonal Variation in Cinchona succirubra Using Random Amplified Polymorphic DNA (RAPD) - Titin Purnaningsih (Universitas Jambi, 2013)
Regenerants of C. succirubra were examined by RAPD analysis to determine theoccurrence and extent of somaclonal variation. Plantlets were regenerated by nodal culture. DNAwas extracted from the parent plant and regenerants of C. succirubra. Fifteen base syntheticoligonucleotides from Operon were chosen that gave multiple polymerase chain reaction (PCR)amplification products using cinchona DNA from parent plants grown in the field and plantlets after 4and 5 passages or 4 and 5 month old in vitro culture. The results showed that all of morphologicalcharacters on regenerated plants were clonally uniform and all of the RAPD profiles were generallymonomorphic, stable, and similar to parent plants. These results demonstrated that RAPD can beused successfully to determine the somaclonal variation among regenerated plants.